EKSPERIMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING , PROBLEM BASED LEARNING, DAN THINK-TALK-WRITE DENGAN PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Umi Supraptinah; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aims of this research were to find out: (1) which one that gives better mathematical problem solving abilities, among learning models of discovery learning (DL), problem based learning (PBL), or think-talk-write (TTW) using scientific approach, (2) which one has better mathematical problem solving abilities, the students having high, medium, or low self regulated learning, (3) in each learning model, which one has better mathematical problem solving abilities, the students having high, medium, or low self regulated learning, (4) in each category of self regulated learning, which one that gives better mathematical problem solving abilities, among learning models of DL, PBL, or TTW using scientific approach. This research was in quasi experimental. The population were all students of grade VIII State Junior High School in Sragen Regency on the second semester of 2014/2015 academic years. The samples were chosen by using stratified cluster random sampling and then selected 296 students. The instruments used for data collection were a questionnaire for self regulated learning of student and mathematical problem solving ability test in the form of essay. Hypothesis testing using two-way ANOVA with unbalanced cells, with a significance level of 5%. The results of research showed as follows. (1) PBL model using scientific approach to provide mathematical problem solving abilities is better than DL and TTW models using scientific approaches, while DL model is better than TTW model; (2) Students with high self regulated learning have mathematical problem solving abilities better than medium or low self regulated learning, while students with medium and low self regulated learning have the same mathematical problem-solving ability; (3) In the DL, PBL, and TTW models using scientific approach, students with high, medium, or low self regulated learning have the same mathematical problem-solving ability; (4) For students with high self regulated learning, the use of DL and PBL models provide the same mathematical problem-solving ability, the DL and TTW models provide the same mathematical problem-solving ability, but PBL model is better than TTW model, for students with medium self regulated learning, PBL model provides mathematical problem-solving ability better than DL and TTW models, while DL and TTW models provide the same mathematical problem-solving ability, for students with low self regulated learning, the use of DL, PBL, and TTW models provide the same mathematical problem-solving ability.Keywords: learning model, discovery learning, problem based learning, think talk write, scientific approach, self regulated learning